Peran Motivasi Kerja dalam Memediasi Pengaruh Lingkungan Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT. Nusantara Electric Tangerang - Aldy Febrian; Yuni Kasmawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the role of work motivation in mediating the influence of work environment and job satisfaction on employee performance of pt nusantara electric. The research method used is descriptive quantitative using a questionnaire. The data analysis technique used in this research is Path Analysis with the Structural Equation Modeling-Partial Least Square approach. Sampling in this study using saturated sampling technique, with a sample size of 58 employees. Data were collected through a questionnaire with a Likert scale which was processed using Microsoft Excel 2016 software and SmartPLS version 4.1.1.2. The results of this study indicate that work environment variables have no significant effect on employee performance. Job satisfaction variables have a positive and significant effect on employee performance. Work environment variables and job satisfaction have a positive and significant effect on work motivation. Work motivation variables have a positive and significant effect on employee performance. Work motivation variables are not able to mediate the effect of work environment on employee performance. Work motivation variables are able to mediate the effect of job satisfaction on employee performance.